2016
DOI: 10.1016/j.soilbio.2015.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of climate warming and elevated CO 2 on autotrophic nitrification and nitrifiers in dryland ecosystems

Abstract: a b s t r a c tGlobal climate change is predicted to enhance atmospheric temperature and CO 2 , with important consequences on biogeochemical nitrogen cycling in dryland ecosystems, which are highly vulnerable and characterized by extremely low nutrient availability. Belowground nitrification processes, predominantly mediated by ammonia-oxidizing archaea (AOA) and bacteria (AOB), are central to plant nitrogen availability and soil N 2 O emissions, but their responses to future climatic scenarios in drylands re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 109 publications
(47 citation statements)
references
References 70 publications
4
43
0
Order By: Relevance
“…Therefore, the high efficiency of metabolism and strong ability to compete for substrates perfectly suit the oligotrophic lifestyle of AOA to thrive in drylands with a constantly low‐level energy supply (He et al ., ; Hu et al ., ). The majority of AOB, however, stay less active or dormant under dry conditions (Hu et al ., 2015b, 2016) and in nutrient‐poor environments (He et al ., ), thus presumably contributing less to N 2 O production in drylands. Although the number of studies is small, it appears that, apart from fungal denitrification, AOA ammonia oxidation may also account for a significantly large portion of dryland N 2 O production during the dry seasons (Fig.…”
Section: Key Biological Pathways Of N2o Emissions In Drylandsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the high efficiency of metabolism and strong ability to compete for substrates perfectly suit the oligotrophic lifestyle of AOA to thrive in drylands with a constantly low‐level energy supply (He et al ., ; Hu et al ., ). The majority of AOB, however, stay less active or dormant under dry conditions (Hu et al ., 2015b, 2016) and in nutrient‐poor environments (He et al ., ), thus presumably contributing less to N 2 O production in drylands. Although the number of studies is small, it appears that, apart from fungal denitrification, AOA ammonia oxidation may also account for a significantly large portion of dryland N 2 O production during the dry seasons (Fig.…”
Section: Key Biological Pathways Of N2o Emissions In Drylandsmentioning
confidence: 99%
“…Dryland‐specific predictions are not universal and readily available, but it has been reported that global warming can reduce the diversity and cover of lichen‐dominated biocrusts, and alter N transformation rates, inorganic N pools (Delgado‐Baquerizo et al ., ) and N 2 O emissions in drylands, and thus induces reinforcing (positive) or stabilizing (negative) feedbacks (Del Grosso and Parton, ). An increase in available N pools (Delgado‐Baquerizo et al ., ) as well as enhanced metabolic activity of N‐cycling microorganisms (Hu et al ., ) under climate warming may further contribute to increased dryland N 2 O emissions. In addition, it was found that the abundance and metabolic activity of AOA and AOB responded differently to warming, with increasing dominance of AOA in nitrification, and thus potentially increasing contribution to N 2 O production, under experimental warming within dryland forest (Hu et al ., ) and grassland soils (Tourna et al ., ).…”
Section: Effects Of Emerging Global Changes On the Biological Pathwaymentioning
confidence: 99%
“…MBC was determined by substrate-induced respiration using gas chromatography (Anderson and Domsch 1978). PNR was measured using the chlorate inhibition soil-slurry method as previously described (Kurola et al, 2005) with modifications (Hu et al, 2016). DEA was quantified as described by Smith and Tiedje (1979).…”
Section: Auxiliary Measurementsmentioning
confidence: 99%
“…Digests were incubated at 37 • C for 3 h, followed by 10 min at 95 • C to deactivate the restriction enzyme. Terminal restriction fragments (TRFs) were resolved on an ABI PRISM 3500 Genetic Analyzer (Applied Biosystems, CA, USA), and processed using Genemapper version 4.0 (Applied Biosystems) as described previously (Hu et al 2015(Hu et al , 2016. The relative fluorescence abundance of all TRFs was exported for downstream analysis.…”
Section: Community Profiling Of the Bacterial 16s Rrna Gene By Terminmentioning
confidence: 99%